Introduction to statistics through resampling methods and R - Good, Phillip I. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"Intended for class use or self-study, the second addition of this text aspires like the first to introduce statistical methodology to a wide audience, simply and intuitively, through resampling from the data at hand. The methodology proceeds from chapter to chapter from the simple to the complex"--
Includes indexes.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Resampling (Statistics); Resampling (Statistics); MATHEMATICS -- Probability & Statistics -- General; Resampling (Statistics); Statistik; Resampling; R; Resampling (Statistics); Electronic books